An adaptive distance protection scheme considering fault resistance, injected current, and structural changes in the power system - Majid Mohtashami; Abbas Saberi Noghabi (IET Generation, Transmission & Distribution)
Abstract Faults in power systems occur for various reasons, such as aging or natural disasters. Detecting, locating, and promptly clearing these faults is crucial for maintaining the safety and reliability of transmission lines (TLs). Distance relays (DRs), which protect TLs, detect faults, estimate their location, and send the required commands. However, these relays may experience mis‐detection due to manipulated impedance arising from both internal and external factors. These factors include measurement device errors, network topology changes, the presence of fault resistance (FR), and injected currents from remote line terminals. To address this challenge, an innovative adaptive protection scheme that considers FR, changes in network topology, and injected current from the opposite end of the line is proposed. By estimating the equivalent circuit impedances (ECIs) of the network connected to the terminal of the TL, this protection scheme utilizes impedance estimation techniques at the line terminals and offline network information. Simulation studies (tested on the IEEE 39‐bus standard network) show that the proposed scheme accurately estimates fault location (FL) and FR with high precision. The simulation results demonstrate its effectiveness in improving the performance of conventional distance protection relays in both the first and second protection zones (Zone1 and Zone2).